A capacity curve model for confined clay brick infills - Özkaynak, Hasan; Yüksel, Ercan; SÜRMELİ, MELİH (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2016)
Experimental studies have proven that clay brick infills, confined with carbon-fiber-reinforced polymers (CFRP) in reinforced concrete (RC) frames, have some advantages in terms of stiffness, strength, energy dissipation capability and damage intensity. Owing to these advantages, existing infill walls in RC frames may be retrofitted with CFRP strips, especially in low-rise buildings in earthquake-prone areas. There is a gap in the literature concerning their behavior model, for use in structural analysis. A piecewise linear capacity curve model called "DUVAR'' is proposed here, which estimates the envelope of force-vs.-displacement hysteresis, depending on the data compiled from the literature and the completed experimental studies. A nonlinear shear spring element is utilized in the model to represent the bare and retrofitted infills. The ultimate shear strength and the corresponding displacement, the ratio of cracking stiffness to initial stiffness, the ratio of ultimate strength to cracking strength, and the ductility ratio are the five key parameters of the model. The model is validated against the experimental results of two sovereign studies. Finally, the model is employed in the performance evaluation of an existing three-story RC building to exemplify its straightforward application.
Keywords: Analytical modeling; CFRP retrofitting; Infill wall; Infilled frame; Shear spring; Rc Frames; Concrete